Mapping Life Cycle Assessment (LCA) scientific research in poultry and feed production - Kássio R. G. Lucas; Ermias Kebreab (Discover Sustainability)
Abstract Propose Population growth and the development of emerging economies have increased the demand for more nutritious foods, such as meat. Poultry farming through the diet diversification, which includes supplements and complementary additives, has developed efficiently, but has implicated in new environmental issues that still need to be better understood. Our objective here was to map the development of environmental impact assessments, notably using the Life Cycle Assessment (LCA), for the poultry and feed sector, identifying the most current trends and gaps. Methods We used bibliometrics for a systematic literature review, using the Scopus repository as database, from 2012 to 2022. To organize and analyze the data, we used the software VOSviewer. Results Environmental evaluations of poultry and feed production have increased annually, as has those using LCA. Although the publication fields vary in terms of whether of LCA is applied, they indicate an important acceptance in the search for information on the environmental impacts of new in techniques poultry farming. However, there is a concentration of studies in regions such as the USA, China, and the European Union. Producers in tropical regions produce fewer studies, although they require information and evaluations specific to their characteristics. LCA has still been little applied to evaluate the impacts of poultry diets, and the evaluations have been focused on greenhouse gas emissions, putting other impact categories aside. The main gap we identified is regarding the LCA use to evaluate the impacts of additives in diets, which is practically non-existent. Conclusion Therefore, the next steps would be to develop LCA to allow it to better assess impacts of the poultry production chain, globally, and to better understand the impacts of feed additives in their diets. Graphical abstract